Strategi Pemanfaatan Konten TikTok dalam Pemasaran Rumah Subsidi: Studi Kasus pada Developer di Pasuruan - Fandy Al Ubaidah; Bayu Hari Prasojo (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The internship program at PT Dewe Makmur Mapan aimed to optimize digital marketing strategies to increase sales of subsidized housing in Pasuruan by targeting Millennials and Generation Z through the TikTok platform. This activity was implemented through content planning based on trend and audience analysis, on-site content production, editing with Search Engine Optimization (SEO) optimization, and publication using the Neulink automation tool. Results over four months showed increased social media engagement, as evidenced by increased user interaction and potential customers contacting marketing via WhatsApp. Educational, informative, and authentic content proved more effective in building consumer trust and interest. This program contributed to increasing the effectiveness of partners' digital marketing and demonstrated that the use of consistent visual content and automation technology has the potential for broader application in the property sector. Thus, social media-based digital marketing is an innovative solution for expanding market reach in the digital era.